2017
DOI: 10.1037/rep0000127
|View full text |Cite
|
Sign up to set email alerts
|

Crip for a day: The unintended negative consequences of disability simulations.

Abstract: Simulating disabilities promotes distress and fails to improve attitudes toward disabled people, undermining efforts to improve integration even while participants report more empathetic concern and "understanding of what the disability experience is like." (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 50 publications
2
80
1
2
Order By: Relevance
“…Disability simulation (DS) has long been used as an experiential learning tool for health science students (Jackle, 1974;Kilbane, 2000;Nario-Redmond et al, 2017). These activities typically consist of students role-playing to experience an impairment directly.…”
Section: Disability Simulation (Ds)mentioning
confidence: 99%
See 2 more Smart Citations
“…Disability simulation (DS) has long been used as an experiential learning tool for health science students (Jackle, 1974;Kilbane, 2000;Nario-Redmond et al, 2017). These activities typically consist of students role-playing to experience an impairment directly.…”
Section: Disability Simulation (Ds)mentioning
confidence: 99%
“…While commonly used as an experiential and active learning strategy, the effectiveness of DS in educating future professionals is inconsistent, often with unintended negative consequences. Research suggests that DS can provide a false sense of "true insight" into disability and evoke sympathy rather than empathy (Nario-Redmond et al, 2017;Silverman, Gwinn, & Van Boven, 2015). Both participants and organizers question the role of DS in educational curricula, recognizing inaccuracies in attempted representations of disability experiences and calling into question their game-like rather than academic exercise execution (Colwell, 2012;Lalvani & Broderick, 2013;Silverman et al, 2015).…”
Section: Disability Simulation (Ds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this type of strategies must be implemented with caution. Research has shown that putting yourself in someone else's shoes might have an opposite effect than intended -it is recommended that more inclusive curricula incorporates contemporary representations of disability, insider expertise, and awareness of strategies for challenging discrimination and promoting disability justice (58). To be able to have disability-related training in universities -and appropriate access to education for students with disabilities -university professors need to be better trained on universal learning design(41)(43) (44).…”
Section: Discussionmentioning
confidence: 99%
“…28 Thirdly, as many disability activists and critical disability studies scholars have argued, simulation exercises not only fail to "simulate" the experience in question, they are actively harmful by reinforcing misguided ableist prejudices. 29 As some who are blind have claimed and as neuroscientific evidence supports, blindness cannot be simulated by a sighted person because blindness is not a lack of sight, but a fundamental set of sensory-physical conditions for the creation of a world. 30 How could one-through a discrete activity, much less a thought experiment-simulate the total, habituated, embodied conditions of an experience of the world?…”
Section: Merleau-ponty's Canementioning
confidence: 99%